Transdiaphragmatic Rupture of Hepatic Abscess Producing Purulent Pericarditis and Pericardial Tamponade. Issue 1 (6th January 2015) - Reddy, Gautam; Chatterjee, Arka; Brott, Brigitta C.
Abstract : Supplemental Digital Content is available in the text.